2023
DOI: 10.1111/1750-3841.16700
|View full text |Cite
|
Sign up to set email alerts
|

Thymol‐loaded Zein–pectin composite nanoparticles as stabilizer to fabricate Pickering emulsion of star anise essential oil for improved stability and antimicrobial activity

Wei Li,
Wenqing Li,
Yulian Wan
et al.

Abstract: The aim of the present study was to prepare a new antimicrobial Pickering emulsion of which the star anise essential oil was added to the oil phase, and to investigate the effect of stabilization by bio‐based active nanoparticles consisting of zein and pectin loaded with thymol. First, the thymol‐loaded zein/pectin composite nanoparticles (ZTNPs) were fabricated as uniformly distributed spherical nanoparticles with an average diameter of 200 nm through antisolvent precipitation. Second, the effects of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, these films exhibited antimicrobial activity against L. monocytogenes in chicken samples at 4 °C for a storage time of 10 days (Xu et al, 2018). Meanwhile, Li et al (2023) used a system based on Pickering emulsion made up of nanoparticles based on Zeina-pectin loaded with thymol, to inhibit the growth of Escherichia coli and Staphylococcus displaying much better results than the control by nearly 7 logs colony-forming unit/g at 36 h (Li et al, 2023).…”
Section: Meatmentioning
confidence: 99%
“…Furthermore, these films exhibited antimicrobial activity against L. monocytogenes in chicken samples at 4 °C for a storage time of 10 days (Xu et al, 2018). Meanwhile, Li et al (2023) used a system based on Pickering emulsion made up of nanoparticles based on Zeina-pectin loaded with thymol, to inhibit the growth of Escherichia coli and Staphylococcus displaying much better results than the control by nearly 7 logs colony-forming unit/g at 36 h (Li et al, 2023).…”
Section: Meatmentioning
confidence: 99%
“…Another limitation is that active essential oils cannot be uniformly added, and their active ingredients may spoil or volatilize during film preparation. Research suggested that Pickering emulsions (PEs) offer a promising solution to meet this challenge [7].…”
Section: Introductionmentioning
confidence: 99%